Economic Prospect Of Fishing Egg Flying for Coastal Communities in Fak Fak District, West Papua Province - Selvi Tebaiy; Paulus Boli; Fanny Simatauw; Simon Leatemia; Dedi Parenden; Andra Ananta (Musamus Fisheries and Marine Journal, 2019)
The economic value of the activity of catching eggs in the waters of the Fak Fak Regency of West Papua not only provides income for migrant fishermen from South Sulawesi but also for the people in the Fak Fak Regency who live in coastal areas. This study aims to provide an overview of the economic impact of flying egg fishing and the marketing channels of these flying fish eggs. Data collection was carried out in August and September 2017 in the coastal areas of Fak Fak and the Fak Fak Fishing Base and several other landing areas. Interview and questionnaire techniques used for data collection also used secondary data from various sources and previous research. The data collected was analyzed descriptively and displayed in graphical form and percentage to reveal facts based on field information. The results showed that in 2017 the production of flying fish eggs per ship ranged from 270 - 1,575 kg, with an average value of IDR 307,446,154. The fish egg marketing channel in Fakfak Regency has 3 main actors namely: producers (fishermen), collecting traders (Papalele) and inter-island traders (Makassar, Takalar). The percentage of costs provided by fly fishing include: (1) fuel and oil 28 %, (2) food supply 26 %, (3) coconut leaves (24 %), and (4) fishing permit (22 %). The economic benefits as an added value from the activity of catching flying fish eggs for the Fak Fak coastal community are the opening of other business opportunities such as coconut leaf providers, fuel and food ingredients providers, boarding or lodging owners, and grater eggs.